(untitled) (Research, Society and Development, 2022)
Introduction: Covid-19 is a multisystemic infection, where late manifestations such as fatigue, dyspnea, loss of aerobic conditioning and muscle mass are common even in patients who have not developed the severe form of the disease, and therefore therapeutic resources are needed to treat these remaining symptoms. Objective: Investigate the immediate repercussions of respiratory physiotherapy techniques performed through a session on patients with a history of Covid-19 in the interior of the Amazon. Methodology: This is a randomized experimental study, with a quantitative-qualitative approach, carried out at the University of the State of Pará. 76 volunteers with a history of Covid-19 participated who were randomized into four groups, one control group and three experimental groups. The three experimental groups were submitted to respiratory physiotherapy techniques and the variables used were the inspiratory pressure (Pimax) and maximum expiratory pressure (Pemax) and the Six-minute walk test (6MWT). Results and Discussion: The results demonstrated the significance of non-invasive ventilation (NIV) on the PiMAX variable in improving inspiratory muscle strength. NIV associated with cycle ergometer and breathing exercises showed significant results in the 6MWT, showing improvement in exercise tolerance. There was no significant result in the comparison between groups. Final considerations: Techniques in respiratory physiotherapy can be beneficial in acquiring exercise tolerance and improving inspiratory muscle strength, but further studies should be encouraged with better methodological designs.